Implementation of Patient Centered Care on Service Quality and Patient Satisfaction: A Literature Review - Putu Agus Sujana Putra; NLP Dina Susanti; I Made Rismawan; Ni Putu Ayu J. Sastamidhayani (Jurnal Keperawatan, 2024)
The concept of Patient Centered Care is a concept that involves patients and families in the process of providing health services with the principles of 4 (four) core concepts, namely paying attention to dignity and respect, sharing information, participation and collaboration. The application of the Patient Centered Care Concept will have an impact on the quality of service and the level of patient satisfaction as a customer. This study aims to explain the effect of implementing patient centered care on improving service quality and patient satisfaction. This study uses the literature review method. Article search uses 3 journal databases from 2019-2023 which were reviewed including Google Scholar, Pubmed and Scient Direct and eleven articles met the criteria. The results of a review of the 11 literatures stated that the higher the application of patient centered care in health services, the higher the patient and family satisfaction. Therefore, it is recommended that the hospital carry out socialization in the form of education on the application of patient centered care on a regular basis to all health workers in the hospital. Health workers in all professions can provide care in accordance with their respective authorities so that the pattern of cooperation between professions can be well established.